Synthesis, Characterization and Biological Evaluation of Novel 1-N-Substituted Thiocarbomoyl-3-ferrocenyl-2-pyrazoline Derivatives - Parveen, Humaira; Suliman Alatawi, Raedah Aiyed; Khan, Salman Ahmad; Al-Ahmdi, Mohammed Issa; Mukhtar, Sayeed; Azam, Amir; Elsayed, Nadia H. (Asian Journal of Chemistry, 2016)
Some novel 1-N-substituted thiocarbomoyl-3-ferrocenyl-2-pyrazoline derivatives were synthesized and evaluated for in vitro antiamoebic activity against HM1:IMSS strain of Entamoeba histolytica. The results showed that most of the compounds exhibited promising activity (IC50 values in the range of 0.050-1.683 μM) than the reference drug metronidazole (IC50 = 1.78 μM). Active compounds were further screened for cytotoxicity against human embryonic kidney-293 (HEK-293) normal cell lines to ensure their toxic effect and the results revealed that active compounds were least toxic in the concentration range of 2.5-50 μM for 48 h and 2.5-25 μM for 72 h. At 100 μM for 48 h and at 50 μM for 72 h only four compounds 2c, 2h, 2k and 2l showed maximum viability and least cytotoxicity, respectively, concluding that all the screened compounds were least cytotoxic against human embryonic kidney-293 (HEK-293) normal cell lines in the concentration range of 2.5-50 and 2.5-25 μM.